Steady-state reaction kinetics of CO oxidation catalyzed by uni-sized Pt30 clusters directly bound to Si surface. Issue 18 (13th July 2016) - Yasumatsu, H.; Fukui, N.
Abstract : Catalytic CO oxidation driven by uni-sized Pt30 bound to a Si substrate, at the interface of which electrons are accumulated. The low-temperature and anti-CO-poisoning performance has been evidenced with continuous and simultaneous supply of CO and O2 . Abstract : The catalytic activities of CO oxidation driven by uni-sized Pt clusters directly bound to a Si substrate surface, Pt30 /Si, are reported. The CO2 production rate was measured as a function of the cluster temperature under steady-state conditions with continuous and simultaneous flow of CO and O2, as well as at fixed reactant exposure followed by a temperature-programmed desorption mass-spectroscopy. The highly selective, sensitive and reliable detection of the catalytic CO2 products allows the determination of the CO oxidation rate against non-negligible background CO2, in spite of the Pt in the catalyst sample being as little as 30 ng. It was demonstrated that Pt30 /Si is a durable and high-performance CO-oxidation catalyst, even when repeating the reaction cycle in coexistence with CO and O2 in the temperature range below 630 K. It is probable that the high performance catalytic activity originates from efficient reductive activation of oxygen by electrons enriched at the subnano-interface between Pt30 and the Si substrate surface.